KINERJA BIDAN DALAM PENANGANAN PERDARAHAN POSTPARTUM DI KABUPATEN JEMBER JAWA TIMUR TAHUN 2011 - Sugijati Sugijati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2012)
Maternal mortality in Jember district was still the highest level in East Java. That was 143/100.000 life-birth in 2010. Hemorrhage caused high maternal death (37,25%) and the highest cause of death among maternal with hemorrhage was postpartum hemorrhage. The objective of this study was to identify factors affecting delima midwives performance for implementing standar of postpartum hemorrhage management in jember district. The study samples were 77 delima midwives was choice by using proportional random sampling method from each area of the subdistrict. Independent variables involved of ability, experience, and motivation. The dependent variables was delima midwives performance for implementing standard of postpartum hemmorhage management. Result of the study showed that, the capability and the respondents experience were moderate and motivation by respondents were good. The relationship factors with delima midwives performance were ability (p=0,000), experience (p=0,000), motivation (P=0,002). It was suggested to the head of district health office to give more opportunity to midwives to continue their education to higher level. Key words : Delima midwives, performance, postpartum hemmorhage.